Establishment of Photosynthesis through Chloroplast Development Is Controlled by Two Distinct Regulatory Phases. Issue 2 (16th June 2017) - Dubreuil, Carole; Jin, Xu; Barajas-López, Juan de Dios; Hewitt, Timothy C.; Tanz, Sandra K.; Dobrenel, Thomas; Schröder, Wolfgang P.; Hanson, Johannes; Pesquet, Edouard; Grönlund, Andreas; Small, Ian; Strand, Åsa
Abstract : The establishment of photosynthesis is a two-phase process with a clear checkpoint associated with the second regulatory phase allowing coordination of the activities of the nuclear and plastid genomes. Abstract: Chloroplasts develop from undifferentiated proplastids present in meristematic tissue. Thus, chloroplast biogenesis is closely connected to leaf development, which restricts our ability to study the process of chloroplast biogenesis per se. As a consequence, we know relatively little about the regulatory mechanisms behind the establishment of the photosynthetic reactions and how the activities of the two genomes involved are coordinated during chloroplast development. We developed a single cell-based experimental system from Arabidopsis ( Arabidopsis thaliana ) with high temporal resolution allowing for investigations of the transition from proplastids to functional chloroplasts. Using this unique cell line, we could show that the establishment of photosynthesis is dependent on a regulatory mechanism involving two distinct phases. The first phase is triggered by rapid light-induced changes in gene expression and the metabolome. The second phase is dependent on the activation of the chloroplast and generates massive changes in the nuclear gene expression required for the transition to photosynthetically functional chloroplasts. The second phase also is associated with a spatial transition of the chloroplasts from clusters around the nucleus to the final position at the cell cortex. Thus, the establishment of photosynthesis is a two-phase process with a clear checkpoint associated with the second regulatory phase allowing coordination of the activities of the nuclear and plastid genomes.